State Ideology, Secularism, and National Identity: Comparing Pancasila and Kemalism in Indonesia and Türkiye - Alia Rizka Mansyur; Muhammad Reyhanmulky; Nabilla Maryam Luthfidyfa; Asy Syifa Azzahra; Inas Fakhirah (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
This study examines how Pancasila and Kemalism shape state ideology and national identity in Indonesia and Türkiye, particularly regarding religion, secularism, and political legitimacy. It employs a qualitative, literature-based approach within comparative political science. The study draws on the constitutional and legal framework of both nations as a primary foundation, but relies heavily on secondary sources, including scholarly works, research articles, and a literature review as the framework. The findings reveal that Pancasila represents an inclusive and accommodative model that integrates religious values within a pluralistic society, while Kemalism reflects a state-led, assertive secularism characterized by a top-down modernization process. Both ideologies are dynamic and subject to reinterpretation in response to contemporary political developments. This study contributes to comparative political analysis by demonstrating how state ideologies function as dynamic instruments for negotiating legitimacy, pluralism, and religion-state relations in Muslim-majority democracies. It offers a novel analytical framework that foregrounds the role of political parties and ideological contestation as drivers of ideological transformation. The research further introduces the concept of “ideological architecture,” highlighting how an ideology is constructed and by whom determines its long-term durability and its capacity to manage the intersection of religion and democracy in Muslim-majority states.